A collection development policy for Dr. Yanga's Colleges, Inc. Basic Education Library (DYCI-BEL) - Dela Cruz, Kevin Dhale S. (School of Library and Information Studies, University of the Philippines Diliman, 2015)
A collection development policy (CDP) is an integral component every school library must-have. By having a concrete CDP, the library will ensure the maintenance of a balanced collection that will substantially answer the information needs of its patrons. Dr. Yanga's Colleges, Inc. Basic Education Library (DYCI-BEL), in light of its parent institution's educational advancements and achievements, does not have its own CDP that will ensure an updated, well-balanced, and responsive in-house collection. Thus, this study aimed to formulate a well-written CDP for the BEL by performing a community needs analysis.